The Demand for (Differentiated) Information - Allen, Beth (Review of Economic Studies, 1986)
A framework for distinguishing between the quantity of information and its quality or type is presented in which information is an indivisible differentiated commodity for which satiation occurs at one unit. Uncountably many types of information are possible which can be costlessly combined by agents. Similarity of information is expressed by a metric which reflects substitution possibilities among different information structures. In the model, traders desire information only because it helps them to maximize state dependent utilities under uncertainty. Then the individual demand for information is well defined, but possibly nonconvex valued because of the indivisibilities.